A Prospective Observational Study on Treatment Evaluation in Patients Newly Diagnosed with Squamous Cell Carcinoma of Head and Neck in Bangladesh - Hai, MA; Haque, Ehteshamul; Reza, Salim; Uddin, Mokhles; Pervin, Kumkum (Anwer Khan Modern Medical College Journal, 2019)
Background: Most head and neck cancers are squamous cell carcinomas (SCCHN) that contribute to substantial morbidity and mortality worldwide. The disease is mostly diagnosed at locally advanced stage. Because treatment of head and neck cancers is complex and involves multiple modalities of surgery, radiotherapy and systemic therapy including chemotherapy and molecularly targeted agents; a multidisciplinary approach is needed. The study evaluated the current treatment approaches for patients newly diagnosed with SCCHN in Bangladesh. Methods: This prospective, observational and non-comparative, study enrolled eligible males and females of 18 years newly diagnosed with SCCHN at any stage of disease. No therapeutic intervention was implied rather selection of treatment strategy and dosage of therapy was on discretion of individual oncologist as per routine clinical practice. Results: A total of 64 patients with median age of 55 years were enrolled between August 2008 and July 2011. The majority of patients (42, 65.6%) were males. The major risk factors were betel leaf chewing along with jorda (smokeless tobacco) (62.5%) and cigarette smoking (32.8%), though most of the patients had multiple risk factors. No patient was diagnosed at early stage; all were in locally advanced disease at stage III (52, 81.3%) and IV (12, 18.8%). The oncologists prescribed neoadjuvant chemotherapy in half (32) of the patients, 19 (29.7%) patients received adjuvant chemotherapy and 13 (20.3%) received palliative chemotherapy. Only 3 (4.6%) of the patients received radiotherapy. Chemotherapy combination regimen included docetaxel, cisplatin and 5-fluorouracil (5-FU) and leucovorin was added to 2 patients. The dosage of chemotherapeutic agents was as per routine clinical practice of the oncologists. Neutropenia was the common hematological abnormality reported spontaneously in 16 (25%) patients. No serious adverse event was reported leading the patients to withdraw from therapy. During continuation of therapy 1 patient died due to sudden cardiac arrest who had medical history of previous myocardial infarction. Conclusion: This registry revealed that squamous cell carcinoma of head and neck region are mostly presented in advanced stage in Bangladesh and the majority of the patients are treated with combination chemotherapeutic regimens. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 17-22